Calculating the Power of Toric Intraocular Lens using Total Corneal Astigmatism Measured by a Swept-Source Optical Coherence Tomography-Based Device: An Observation which Changed our Practice Pattern - Sanjay Chaudhary; Alka Pandey; Anju Sharma; Rahil Chaudhary; Hema Mehra; Nishtha Khurana; Divya Vermani; Ritu Nagpal (Delhi Journal of Ophthalmology)
Toric intraocular lenses (IOLs) have been a game-changer for addressing patients with cataract and significant preexisting corneal astigmatism. With increasing demands and expectations of the patients, there is now a greater responsibility on part of anterior segment surgeons to offer a postoperative uncorrected visual acuity of 6/6. At present, majority of surgeons rely on the “measured” values of anterior corneal astigmatism and “predicted” values of posterior corneal astigmatism to calculate the final IOL power and the axis of the toric IOL. Such a practice, at times, has been shown to result in unexpected postoperative refractive outcomes. We have had situations where the anterior corneal curvature values suggested using a spherical IOL, while the measured total corneal astigmatism values suggested implanting a toric IOL to minimize the postoperative residual astigmatism. Not only this, we also encountered situations where the axis of the anterior corneal curvature is not in concordance with that of the total corneal power. Differences as high as 8° have been witnessed. Implanting a toric IOL solely based on the magnitude and axis of the anterior corneal astigmatism would have resulted in residual astigmatic errors. In this article we intend to elaborate on the available literature regarding the contribution of the posterior corneal surface toward the total corneal power. We would also provide some of our clinical scenarios which changed our practice pattern for IOL calculations and discuss future applications of this information.